Economic Analysis for Rebuilding of an Aged Pulverized Coal-Fired Boiler with a New Boiler in an Aged Thermal Power Plant - Cetin, Burhanettin; Abacioglu, Merve (HINDAWI PUBLISHING CORPORATION, 2013)
Fossil-fired thermal power plants (TPP) produce a significant part of electricity in the world. Because of the aging TPPs and so their equipment (especially boiler), thermal power plants also produce less power than their installed capacities, and there has been power loss in time. This situation affects the supply and demand balance of countries. For this reason, aging equipments such as pulverized coal-fired boiler (PCB) must be renewed and power loss must be recovered, instead of building new TPPs. In this study, economic analysis of rebuilding an aged pulverized coal-fired boiler with a new pulverized coal-fired boiler including flue gas desulfurization (FGD) unit and a circulating fluidized bed boiler (FBB) are investigated in an existing old TPP. Emission costs are also added to model, and the developed model is applied to a 200 MWe pulverized coal-fired thermal power plant in Turkey. As a result, the payback period and the net present value are calculated for different technical and economic parameters such as power loss, load factor, electricity price, discount rate, and escalation rate by using the annual value method. The outcomes of this study show that rebuilding of a pulverized coal-fired boiler with a new one is amortized itself in a very short time.
Keywords: EXTERNAL COSTS; COMBUSTION; Thermodynamics; Engineering